2018
DOI: 10.5603/imh.2018.0038
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risk perception, stressors and stress of fishermen

Abstract: Background: The aim of this survey was to assess the stress in fishermen by analysing its relationship with sociodemographic and professional characteristics, by evaluating work stressors, and by estimating psychosomatic symptoms. Materials and methods: This cross-sectional survey involved representative sample of 828 artisanal and coastal fishermen. All participants were men and had a regular activity for at least 2 years. We used an individual questionnaire inspired by those of the National Institute for Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…They claimed that fishermen compensate a decrease in alertness and an increase in fatigue through the consumption of substances such as alcohol. This consumption increases among fishermen with stress as compared to those without stress [10]. In contrast, Slišković and Penezić [15] found that stress on board was mainly related to a lack of sleep and an unhealthy diet, two factors that cannot be directly influenced by the seafarers [15].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…They claimed that fishermen compensate a decrease in alertness and an increase in fatigue through the consumption of substances such as alcohol. This consumption increases among fishermen with stress as compared to those without stress [10]. In contrast, Slišković and Penezić [15] found that stress on board was mainly related to a lack of sleep and an unhealthy diet, two factors that cannot be directly influenced by the seafarers [15].…”
Section: Discussionmentioning
confidence: 92%
“…The investigation of alcohol consumption in connection with stress did not reveal a clear tendency, based on the results in two of 3 studies. Only Laraqui et al [10] showed a significant association between alcohol consumption and stress. They claimed that fishermen compensate a decrease in alertness and an increase in fatigue through the consumption of substances such as alcohol.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations